"Chlorine Sweeps" Save Time, Money in Hunt for Closed Valves. Issue 3 (5th March 2020) - Nebgen, Wesley; Lavake, Thomas; Klidies, Jennifer
Abstract : Utility staff in Corpus Christi, Texas, developed a method to identify unexpectedly closed valves that affect water quality. By analyzing changes in chlorine residuals from selected hydrants and mapping the data, staff can verify the valves' position and open them, improving quality and system hydraulics.